PENINGKATAN REGULASI MAHASISWA PPG MELALUI AKTIVITAS PENGEMBANGAN PERANGKAT PEMBELAJARAN - Ivan Stevanus; Clara Ika Sari Budhayanti; Theresia Agnes Wijaya (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
The development of learning tools aims to facilitate students to design innovative learning activities by utilizing the results of analysis of problem-based, literacy and HOTS teaching materials. Project-Based Learning is aimed at improving high-level thinking skills, understanding problems and strengthening literacy. This classroom action research describes increasing the regulatory abilities of PPG students in using Project Based Learning (PjBL). This research was carried out in two cycles. The research results show that Project Based Learning (PjBL) model learning through the Learning Management System can improve the regulatory abilities of Teacher Professional Program (PPG) students. In the first cycle, the achievement of indicators of student regulatory success reached the quite good category with a percentage of 71%. In the second cycle of action, PPG students' regulatory abilities increased to the good category with a percentage achievement of 76%. It can be concluded hat self-regulation abilities to increase and be consistent, the implementation of Project Based Learning can be carried out in three cycles and reinforced with various learning topics in the Learning Management System (LMS). This effort is important with a focus on improving aspects of self-regulation capabilities, namely deepening essential questions, strengthening plans and implementation of HOTS-based projects.